Development of a Computer-Aided Teaching and Learning Tool for Digital Filters Using Agilent VEE PRO 6.0 - Ibrahim, Hamimah (2010)
Digital filters play very important roles in digital signal processing (DSP). There are many types of digital filters. The objective of this work is to develop a program with added functionality for an oscilloscope and data acquisition card (NI-DAQ card) using filters. The development system utilized an oscilloscope, data acquisition card (NI-DAQ card), function generator and Agilent VEE PRO 6.0. All data acquisition, control and analysis were accomplished using Agilent VEE PRO 6.0. Six most common filters are demonstrated in this work. The signal source was a ETS-7000 Digital-Analog Training System signal generator. The output of the ETS-7000 Digital-Analog Training System signal generator was connected to channel 1 of the HP54602B oscilloscope. Data acquisition and control of the HP54602B and NI-DAQ card was realized using the Agilent VEE PRO 6.0 by using RS-232 send port communication. The Agilent VEE PRO 6.0 was also used for data analysis and presentation. In addition, the Agilent VEE PRO 6.0 was also used to display simultaneously both signals before and after applying signal processing.